Secondhand smoke exposure and behavioral problems in Japanese schoolchildren - Hata, Toshiki; Ishida, Haruhi; Inoue, Hiroko; Hashimoto, Ayako; Morimoto, Yukina; Nagaya, Ikuko; Nakamura, Kozue; Kuwano, Toshiko (Frontiers in Public Health, 2025)
IntroductionEvidence on the association between secondhand tobacco smoke exposure and behavioral problems in schoolchildren remain limited. This study examined the association between objectively measured secondhand smoke exposure and behavioral problems among Japanese schoolchildren.MethodsThis study included 892 schoolchildren (444 boys, 448 girls) in Yamagata City, Gifu, Japan. Secondhand smoke exposure was assessed using urinary creatinine-corrected cotinine concentration (UC), with levels <5.0 ng/mgCr classified as low and ≥5.0 ng/mgCr as high. Behavioral problems were evaluated using the Strengths and Difficulties Questionnaire (SDQ), completed by guardians. Multivariate-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by grade level.ResultsAmong participants, 10.1% (n = 41) in the early grades and 7.4% (n = 36) in the upper grades had high UC. In the upper grades, the OR for behavioral problems was significantly higher in those with high UC (OR: 2.39, 95% CI: 1.05–5.45). Additionally, Hyperactivity, Conduct problems, and Prosocial behavior were significantly worse in students with high UC. However, in the early grades, no significant association was observed between high UC and behavioral problems (OR: 1.04, 95% CI: 0.45–2.40), except for emotional symptoms, which were significantly worse in children with high UC.DiscussionSecondhand smoke exposure may increase the risk of behavioral problems in Japanese schoolchildren, particularly in the upper grades. Reducing exposure, especially at home and in the community, should be prioritized to prevent behavioral and psychological problems.